The ’new Englishes’ - Baskaran, Loga Mahesan (Journal of Modern Languages, 2017)
It is apparent and undeniable, therefore, that the New Englishes are well past the evolution stage - although it is also undeniable that language is always never in a ’freeze frame’ so to speak. The New Englishes, however, have passed their formative years, and coupled with the fact that they are wholesomely accepted by their speakers - the need for complete recognition is past denying here, and as the saying goes, "The best may be the enemy of the good" let not standard British English put off any of these New Englishes, all that is asked for is tolerance towards them as Charles Taylor (1984) says, "While with languages in general, we should teach the language, and not about the language: with varieties, the reverse is true: teach about varieties - but never attempt to teach them".